What Drives the Adoption of Virtual Influencers in Indonesia? A TAM2 Perspective on Social Influence and Cognitive Absorption - Agung Stefanus Kembau; Devi Yurisca Bernanda; Arief Perdana Kumaat; Fidelia Novena Doa (Economics and Digital Business Review, 2025)
The rise of Virtual Influencers (VIs) in digital marketing has revolutionized the way brands engage with consumers, yet the underlying factors that drive their adoption and interaction remain largely unexplored, particularly in emerging markets such as Indonesia. This study delves into the Behavioral Intention to Use (BIU) Virtual Influencers, applying the Technology Acceptance Model 2 (TAM2) to identify key determinants like Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Social Influence (SI), and Facilitating Conditions (FC). Furthermore, the research investigates the mediating roles of Attitude Toward Using (ATU) and Cognitive Absorption (CA). Through an online survey of 198 Indonesian social media users familiar with AI applications, the results reveal that PU and PEOU directly influence ATU, which in turn significantly shapes BIU. SI and FC exert both direct and indirect effects via ATU and CA. These findings highlight the critical role of cognitive and social factors in driving consumer engagement with VIs in Indonesia, offering valuable insights for businesses aiming to capitalize on this emerging trend. The study extends traditional technology adoption models, calling for further exploration of cultural dynamics and long-term impacts on consumer behavior.